New Methods for Reducing the Problems of Photovoltaic Systems - Sobhan Dorahaki (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Increasing of demand in the energy sphere and also unprecedented proliferation of environmental pollutants in the air has pushed human toward the using of renewable energy sources such as photovoltaic systems. Unfortunately, despite all the efforts made, in the field of photovoltaic systems, still the usability of this clean and renewable source is skeptical in the world. This paper examines some basic problems of photovoltaic systems and discusses a few new approaches to reduce some problems of photovoltaic systems. The proposed approaches have capabilities and difficulties which are investigated in this study.